Closed Synthetic Cycle for Nickel-Based Dihydrogen Formation - Hosseinmardi, Soosan; Scheurer, Andreas; Heinemann, Frank Wilhelm; Marigo, Nicola; Munz, Dominik; Meyer, Karsten (Chemistry - A European Journal, 2023)
Dihydrogen evolution was observed in a two-step protonation reaction starting from a Ni0 precursor with a tripodal N-heterocyclic carbene (NHC) ligand. Upon the first protonation, a NiII monohydride complex was formed, which was isolated and fully characterized. Subsequent protonation yields H2 via a transient intermediate (INT) and an isolable NiII acetonitrile complex. The latter can be reduced to regenerate its Ni0 precursor. The mechanism of H2 formation was investigated by using a deuterated acid and scrutinized by 1H NMR spectroscopy and gas chromatography. Remarkably, the second protonation forms a rare nickel dihydrogen complex, which was detected and identified in solution and characterized by 1H NMR spectroscopy. DFT-based computational analyses were employed to propose a reaction profile and a molecular structure of the Ni−H2 complex. Thus, a dihydrogen-evolving, closed-synthetic cycle is reported with a rare Ni−H2 species as a key intermediate.
CRIS-Team Scopus Importer:2023-10-20
Keywords: H; NHC; nickel complexes; nickel dihydrogen; nickel hydride